Measurements of the quadrupole strengths in the N → Δ transition at Mainz and Bates - Sparveris, N. F. (HNPS Advances in Nuclear Physics, 2020)
The issue of hadron deformation has been a subject of intense scientific interest during the last two decades. The detailed study of the N → Δ transition is the best method of experimental investigation of this issue. The most recent results from the Bates and Mainz N → Δ programs will be presented which focus at the low Q2 region. The experimental data yield precise non zero quadrupole to dipole amplitude EMR and CMR ratios, giving credence to the conjecture of deformation in hadrons favoring the attribution of the origin of deformation at the low Q2 region to the dominance of mesonic effects.